Adaptin evolution in kinetoplastids and emergence of the variant surface glycoprotein coat in African trypanosomatids. - Manna, P; Kelly, S; Field, M (2013)
The kinetoplastids are an important group of protozoa from the Excavata supergroup, and cause numerous diseases with wide environmental, economic and ecological impact. Trypanosoma brucei, the causative agent of human African trypanosomiasis, expresses a dense variant surface glycoprotein (VSG) coat, facilitating immune evasion via rapid switching and antigenic variation. Coupled to VSG switching is efficient clathrin-mediated endocytosis (CME), which removes anti-VSG antibody from the parasite surface. While the precise molecular basis for an extreme CME flux is unknown, genes encoding the AP2 complex, central to CME in most organisms, are absent from T. brucei, suggesting a mechanistic divergence in trypanosome CME. Here we identify the AP complex gene cohorts of all available kinetoplastid genomes and a new Trypanosoma grayi genome. We find multiple secondary losses of AP complexes, but that loss of AP2 is restricted to T. brucei and closest relatives. Further, loss of AP2 correlates precisely with the presence of VSG genes, supporting a model whereby these two adaptations may function synergistically in immune evasion.